Mixed Ensemble Learning Through the Problem Based Learning Model in Grade VII of SMP Negeri 4 Batang Hari Leko Muba - Egik Depriasi; Nofroza Yelli; Deria Sepdwiko (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to determine the learning process of mixed ensembles using the Problem-Based Learning model in seventh-grade students at SMP Negeri 4 Batang Hari Leko, Muba. In this lesson, students were divided into several groups using pianicas, buckets, glasses, spoons, maracas (rice-filled bottles), and small kolintang instruments. The material was the song "Apuse." The Problem-Based Learning model was implemented by presenting students with problems, then asking them to work together in groups to find solutions, practice together, and present to the class for grades. The method used in this study was descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The subjects were seventh-grade arts and culture teachers at SMP Negeri 4 Batang Hari Leko, Muba. The results showed that the Problem-Based Learning model can improve student cooperation, activeness, and self-confidence. Students became more confident in expressing their opinions and were able to work together in groups.